Spontaneous Tumor Lysis Syndrome due to Uterine Leiomyosarcoma with Lung Metastases - Vivek Alaigh; Debapriya Datta (Case Reports in Critical Care)
Tumor lysis syndrome (TLS) is an oncologic emergency characterized by a combination of metabolic derangements (hyperuricemia, hyperkalemia, hyperphosphatemia, and hypocalcemia) caused by rapid turnover from cell destruction in certain cancers. These metabolic derangements can lead to seizures, cardiac arrhythmias, renal failure, and death. TLS is usually seen after the initiation of chemotherapy for hematologic malignancies. TLS occurring spontaneously, without initiation of chemotherapy, is rare and its occurrence in solid tumors is rarer still. We report a case of spontaneous TLS in a patient with leiomyosarcoma of the uterus, with metastasis to lung. Such a case has never been reported before.